Nitrifying and heterotrophic population dynamics in biofilm reactors: effects of hydraulic retention time and the presence of organic carbon - Nogueira, R. (2002)
Two biofilmreactors operated with hydraulic retention times of 0.8 and 5.0 h were used to study the links between population dynamics and reactor operation performance during a shift in process operation from pure nitrification to combined nitrification and organic carbon removal. The ammonium and the organic carbon loads were identical for both reactors. The composition and dynamics of the microbial consortia were quantified by fluorescence in situ hybridization (FISH) with rRNA-targeted oligonucleotide probes combined with confocal laser scanning microscopy, and digital image analysis. In contrast to past research, after addition of acetate as organic carbon nitrification performance decreased more drastically in the reactor with longer hydraulic retention time. FISH analysis showed that this effect was caused by the unexpected formation of a heterotrophic microorganism layer on top of the nitrifying biofilm that limited nitrifiers oxygen supply. Our results demonstrate that extension of the hydraulic retention time might be insufficient to improve combined nitrification and organic carbon removal in biofilm reactors.